ANALYSIS DU PONT SYSTEM IN MEASURING COMPANY FINANCIAL PERFORMANCE (CASE STUDY OF TELECOMMUNICATION COMPANIES LISTED ON THE IDX IN 2016-2021) - AYU LESTARI; MUHAMMAD FAUZAN (MANKEU (JURNAL MANAJEMEN KEUANGAN), 2023)
This research was conducted to measure the financial performance of telecommunications companies listed on the Indonesia Stock Exchange. The purpose of this study is to find out and analyze the financial performance of telecommunication companies listed on the IDX in 2016-2021 using the method Dupont system. Research population conducted by researchers are 6 companies in the field of telecommunications. The sample of this research using purposive sampling method is 5 telecommunication companies with 6 years period. The data analysis used in this study used a descriptive method with a quantitative approach and to measure financial performance in this study the test tool used was analysisDupont system using industry averagesNet Profit Margin (NPM), Total Asset Turnover (TATO) and Return On Investment (ROI) (Du Pont) throughout the period of the company as a comparison of performance in each company. The results of the study show that the financial performance of telecommunications companies listed on the Indonesia Stock Exchange is calculated using Dupont system yet good, with valueReturn On Investment (ROI) (Du Pont) decrease. This is due to a decrease in value Net Profit Margin (NPM) andTotal Assets Turnover (TATO) in every company. Of the five companies studied, namely PT Bakrie Telekom Tbk, PT Indosat Tbk, PT Smartfren Tbk, PT XL Axiata Tbk, and PT Telekomunikasi Indonesia Tbk, the ROI value (Du Pont) only PT.XL Axiata Tbk whose financial performance is quite good because of the ROI value (Du Pont) has a dominant value above the company's industry average. PT.XL Axiata Tbk is included in the company whose financial performance is in good criteria.